Diabetic Ketoasidosis - Dela Serlina (Rifa'Institute, 2021)
Diabetic ketoacidosis (DKA) is one of the acute complications for diabetics that usually occurs in type 1 DM, but it is possible in type 2 DM. DKA is caused by a decrease in effective insulin circulation associated with an increase in counter-regulatory hormones. The incidence of DKA ranges from 0 to 56 per 1000 people each year. In Indonesia, it is known that 71% of pediatric patients have DKA as the initial clinical presentation of type-1 DM in 2017. To know more about diabetic ketoacidosis. Knowing the characteristics of patients with diabetic ketoacidosis. Know how to treat patients with diabetic ketoacidosis. This reserch use Literatur-review method. DKA is a complication of uncontrolled type 1 diabetes mellitus and has a high risk of being life-threatening. The incidence of DKA in Indonesia is not known for certain, but it is estimated at 76.9% based on data from Riskesdas in 2007. DKA occurs due to insulin deficiency which will result in increased lipolysis and usually occurs due to metabolic stress conditions. Symptoms of DKA are symptoms of hyperglycemia and classic symptoms of hyperglycemia. The key to the diagnosis of DKA is an increase in total circulating ketone bodies. The initial management of DKA is to monitor and secure the airway, breathing, circulation.